A sensitive and rapid method for quantification of lacosamide and desmethyl lacosamide by LC–MS/MS. (December 2014) - Payto, Drew; Foldvary-Schaefer, Nancy; So, Norman; Bruton, Monica; Wang, Sihe
Background: Monitoring lacosamide (LCM) helps optimize therapeutic dosing in some clinical settings. We developed a novel LC–MS/MS method for measuring serum LCM and O-desmethyl lacosamide (ODL).Results/discussion: The sample preparation was protein precipitation with methanol. The total CV was less than 4.7%. Calibration range was 0.95–30.29 µg/ml and 0.95–30.41 µg/ml while the expanded linear range was 0.41–47.49 µg/ml and 0.34–48.17 µg/ml for LCM and ODL, respectively with analytical accuracy of 87.2–106.0%. 45 random serum samples collected from 23 individuals on either 200 mg/day or 400 mg/day of LCM therapy showed concentrations of 2.2–19.8 µg/ml for LCM and up to 2.5 µg/ml for ODL.Conclusion: A simple and sensitive LC–MS/MS assay was validated for quantification of LCM and ODL in human serum.